Comparison of the quality of beef from Jagalan RPH Production and Non-RPH Production - Pramudita, Ayu; Indrowati, Meti (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2025)
Meat quality is determined based on aspects of handling, inspection, environment and facilities at the slaughterhouse. Some of these aspects have been paid attention to by slaughterhouses (RPH), but they are still less of a concern for places that carry out independent slaughtering. The aim of this research is to determine the difference in the quality of meat from RPH production and meat from production other than RPH. Parameters used in meat quality testing include organoleptic tests (color, odor, consistency and cleanliness), pH tests and Water Holding Ability (DIA) tests. Data were analyzed using the Kruskal Wallis test, if there were significant differences, it was continued with the Mann Whitney test. The results showed that there were significant differences in color quality, consistency, pH and DIA values (P<0.05). Meanwhile, the results did not show significant differences in bau and cleanliness parameters (P>0.05). However, meat originating from both places is still at a level suitable for consumption